Figurative Language in Song Lyrics of the Essential Album by John Denver: Semantics Study - Novika Angel Simatupang; Ida Zuraida Supri (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
The aims of this study are 1) to analyze the types of figurative language found in “Song Lyrics of the Essential Album by John Denver”, and 2) to analyze the meanings that appeared in "David Campbell’s Poem “Night Sowing”. The method used for this research is qualitative-descriptive. The data were taken from “Song Lyrics of the Essential Album by John Denver as many as 32. The theory used for analyzing the types of figurative language is Peter (2020). The findings of this research indicate that the types of figurative language are divided into 3 types which are, the simile is 5 data, hyperbole is 11 data, personification is 12 data, and metaphor is 2 data. However, the use of Figurative Language that is often used in this album is personification Figurative Language which amounts to twelve data, and the use of Figurative Language which is less used metaphorical Figurative Language which amounts to only two data. The meanings contained in the song lyrics in the album The Essential John Denver are as follows: connotative meaning as 8 data, denotative meaning as much as 18 data, and contextual meaning as many as 4 data, it can be concluded that the meaning that is often used in song lyrics in the album is a denotative meaning which consists of 18 data.